DETERMINASI SISTEM PENGENDALIAN INTERNAL, TEKNOLOGI INFORMASI, KOMPETENSI APARATUR DAN KOMITMEN ORGANISASI PADA PENGELOLAAN DANA DESA: DETERMINATION OF INTERNAL CONTROL SYSTEM, INFORMATION TECHNOLOGY, APPARATUS COMPETENCY AND ORGANIZATIONAL COMMITMENT IN VILLAGE FUND MANAGEMENT - Alfiatri, Wina; Indrawati, Novita; Putra, Adhitya Agri (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
The goal of this study is to determine and test the impact of internal control systems, information technology use, apparatus competency, and the organization's commitment to village fund management. This study took place in the villages of Kuantan Singingi Regency's Cerenti Subdistrict. The population of 11 villages in Kuantan Singingi Regency's Cerenti Subdistrict was studied. A saturation sampling method is a sampling approach in which all members of the population are used as samplers. Respondents in this study were village apparatus in Cerenti Subdistrict, Kuantan Singingi Regency. Internal control systems, information technology utilization, apparatus competency, and organizational commitment all have a substantial impact on village fund administration, according to data analysis utilizing multiple linear regressions. The results of this study are expected to be a suggestion for the village government, especially the village apparatus in Cerenti Subdistrict in improving village fund management by paying attention to the factors studied in this study.